2017
DOI: 10.1145/3132700
|View full text |Cite
|
Sign up to set email alerts
|

Declarative Probabilistic Programming with Datalog

Abstract: Probabilistic programming languages are used for developing statistical models, and they typically consist of two components: a specification of a stochastic process (the prior), and a specification of observations that restrict the probability space to a conditional subspace (the posterior). Use cases of such formalisms include the development of algorithms in machine learning and artificial intelligence. We propose and investigate an extension of Datalog for specifying statistical models, and establish a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 54 publications
2
69
0
Order By: Relevance
“…Let F be a collection of disjoint measurable fact sets. It has to be shown that the events (E F ) F ∈F are independent (i. e., (7) holds). To see this, we show the independence of (E F ) F ∈F ′ where E F = Ω − E f .…”
Section: Tuple-independence In the Infinitementioning
confidence: 99%
“…Let F be a collection of disjoint measurable fact sets. It has to be shown that the events (E F ) F ∈F are independent (i. e., (7) holds). To see this, we show the independence of (E F ) F ∈F ′ where E F = Ω − E f .…”
Section: Tuple-independence In the Infinitementioning
confidence: 99%
“…As discussed in detail later in Section 6, we believe that modern needs require the enhancement of the database technology with machine learning capabilities. In particular, an important challenge is to combine the two key capabilities (machine learning and data) via query languages for building statistical models, as already began by initial efforts [23,35]. Reasoning.…”
Section: Rdbms Technology In the Presence Of Incomplete Datamentioning
confidence: 99%
“…For example, by applying the notion of the Vapnik-Chervonenkis dimension, an important theoretical concept in generalization theory, to database queries, Riondato et al [121] provide accurate bounds for their selectivity estimates that hold with high probability; moreover, they show the error probability to hold simultaneously for the selectivity estimates of all queries in the query class. In general, this direction can leverage the past decade of research on probabilistic databases [47,90,23,91], which can be combined with theoretical frameworks of machine learning, such as PAC (Probably Approximately Correct) learning [139].…”
Section: Data Management and Machine Learningmentioning
confidence: 99%
“…InsideOut is a component of LogicBlox's effort to extend LogiQL to be a probabilistic programming language [10], as part of DARPA's PPAML and MUSE programs. The component the algorithm handles is inference in discrete graphical models.…”
Section: Practical Implicationsmentioning
confidence: 99%